ANALISIS KONTEN VICTIM BLAMING DALAM FILM AIR MATA DI UJUNG SAJADAH KARYA KEY MANGUNGSONG - Lestari, Susan Farma Ayu; Irawan, Dody; Habiba, Siti; Wahyusari, Ahada; Lolita, Asri; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and describe the forms of victim blaming represented in the film. The research uses a qualitative approach with a descriptive method. Data sources include dialogues, speech, and scenes that contain elements of victim blaming in the film Air Mata di Ujung Sajadah. Data were collected using observation and note-taking techniques with the help of a data corpus sheet, then analyzed using a literary sociology approach based on genetic structuralism theory, which includes human facts, social facts, collective subjects, and worldview. The results show that the practice of victim blaming appears in the form of negative labeling of victims, shifting responsibility onto the victims, social exclusion, and using the victims past experiences to justify the treatment they received. This representation is shown through both verbal and nonverbal elements that reflect the dominance of patriarchal culture and the imbalance of power relations within the family. In this way, the film Tears at the End of the Prayer Mat not only presents a depiction of victim blaming practices but also offers a critique of the culture of blaming victims and encourages society to grow awareness in respecting the rights and dignity of victims.